2017
DOI: 10.1177/0149206316681846
|View full text |Cite
|
Sign up to set email alerts
|

Applicant Perspectives During Selection: A Review Addressing “So What?,” “What’s New?,” and “Where to Next?”

Abstract: We provide a comprehensive but critical review of research on applicant reactions to selection procedures published since 2000 (n = 145) Table S1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
216
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(242 citation statements)
references
References 163 publications
(312 reference statements)
5
216
0
7
Order By: Relevance
“…The results of our study show that explanations emphasizing the advantages of standardization and flexibility of video interviews can have positive effects on fairness perceptions and perceived usability and thereby also indirectly on applicant reactions. This is in line with previous evidence on the beneficial effects of explanations concerning other selection procedures (McCarthy, Bauer, Truxillo, Anderson, et al, 2017;Truxillo et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of our study show that explanations emphasizing the advantages of standardization and flexibility of video interviews can have positive effects on fairness perceptions and perceived usability and thereby also indirectly on applicant reactions. This is in line with previous evidence on the beneficial effects of explanations concerning other selection procedures (McCarthy, Bauer, Truxillo, Anderson, et al, 2017;Truxillo et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…However, this effect is similar to Chapman and Rowe (2002) who found that participants accepted higher structure in videoconference interviews more than they did in FTF interviews. Additionally, it is also noteworthy that we even found larger effects of expla-Personnel Assessment And decisions APPlicAnt reActions to Video interViews Besides previous studies that found that explanations can improve fairness perceptions of selection procedures (McCarthy, Bauer, Truxillo, Anderson, et al, 2017), our study also sheds new light on the fact that explanations can also improve perceptions beyond fairness such as perceived flexibility or perceptions of usability that are related to Davis' (1989) technology acceptance model. Furthermore, these perceptions can indirectly affect the perceived attractiveness of an organization in addition to fairness perceptions.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This study examined test performance and applicant reactions as two relevant outcomes. Candidates who perform poorly are less likely to be hired and applicant reactions are related to important job relevant attitudes, intentions, and behaviors (see McCarthy et al, (2017) for a comprehensive review). Our results suggest that interruptions are moderately negatively related to test performance.…”
Section: Personnel Assessment and Decisionsmentioning
confidence: 99%
“…One can imagine a manager reading about brainteasers in the popular press and deciding to throw in a question or two in his or her own interview. The costs of using assessment tools that are aversive to applicants, however, include reduced job‐pursuit intentions, negative word‐of‐mouth about the organisation, and possibly misleading performance on the assessment itself (see McCarthy, Bauer, Truxillo, Anderson, Costa, & Ahmed, , for a review).…”
mentioning
confidence: 99%